The biodiversity of macroalgae in the coastal waters of Tongkaina, Manado City - Kepel, Rene Charles; Mantiri, Desy M. H.; Nasprianto, - - (Sam Ratulangi University, 2018)
This study was carried out in coastal waters of Tongkaina, Manado City with an objective of knowing the taxa composition of macroalgae through morphological studies. Data collection used exploring survey. Results found 15 species that consisted 7 species of green algae, 4 species of brown algae, and 4 species of red algae.Keyword: Macroalgae, Tongkaina. Â AbstrakPenelitian ini dilakukan di perairan pesisir Tongkaina, Kota Manado dengan tujuan untuk mengetahui komposisi taksa makroalga melalui pendekatan morfologi. Pengambilan data dilakukan dengan menggunakan metode Survei Jelajah. Hasil penelitian menemukan 15 spesies, yang terdiri dari 7 spesies alga hijau, 4 spesies alga cokelat dan 4 spesies alga merah.Kata Kunci: makroalga, Tongkaina.